2015
DOI: 10.1093/esr/jcu093
|View full text |Cite
|
Sign up to set email alerts
|

Racial Preferences in Online Dating across European Countries

Abstract: Knowledge about how race governs partner selection has been predominantly studied in the United States, yet it is unclear whether these results can be generalized to nations with different racial and immigration patterns. Using a large-scale sample of online daters in nine European countries, we engage in the first cross-national analysis of race-related partner preferences and examine the link between contextual factors and ethnic selectivity. We provide a unique test of contact, conflict, and ingroup identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 64 publications
1
45
0
4
Order By: Relevance
“…A more careful look at the different intermarriage combinations according to the origin of the immigrant partner reveals more complex patterns that are congruent with native women's preferences having a more rigid ethnic hierarchy than those of native men, as argued by Potârcă and Mills (2015). First of all, intermarriage with Moroccan men, the most stigmatized immigrants especially from a female perspective, seems to be reserved for inactive, unemployed, and low-skilled native women.…”
Section: Discussionmentioning
confidence: 85%
“…A more careful look at the different intermarriage combinations according to the origin of the immigrant partner reveals more complex patterns that are congruent with native women's preferences having a more rigid ethnic hierarchy than those of native men, as argued by Potârcă and Mills (2015). First of all, intermarriage with Moroccan men, the most stigmatized immigrants especially from a female perspective, seems to be reserved for inactive, unemployed, and low-skilled native women.…”
Section: Discussionmentioning
confidence: 85%
“…A few studies found only limited support for the discrimination of Turkish minorities in the market for student housing (Diehl, Andorfer, Khoudja, & Krause, 2013) and in public administration when requesting information on childcare and mobile homes (Grohs, Adam, & Knill, 2016). They share a high level of discrimination with Arab minorities in the Western hemisphere (e.g., Blommaert, Coenders, & van Tubergen, 2014;Gaddis & Ghoshal, 2015;Potârcă & Mills, 2015). Recently, Tjaden, Schwemmer, and Khadjavi (2018) analysed the clicking behaviour on one of Europe's largest carpooling websites and discovered that drivers with Arabic/Turkish and Persian names were less often selected as potential drivers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Výhodou ukazatelů, jako je vzdělání, věk, etnická příslušnost nebo náboženské vyznání, je jejich snadná dostupnost v dotazníkových šetřeních: evidenci pro ně máme z reprezentativních výzkumů od Asie [Smits, Park 2009] přes Evropu [Hamplová 2009] po USA [Smits, Ultee, Lammers 1998]. Z longitudinálních šetření [Dribe, Nystedt 2013], výzkumu partnerských preferencí [Katrňák et al 2010] a nově i dat z online seznamování [Potarca, Mills 2015] máme doklady, že výběrové párování v těchto ukazatelích zřejmě nevzniká náhodně, ale že jednotlivci volí partnera, který se jim sociodemograficky podobá.…”
Section: úVodunclassified
“…V současné sociologické literatuře jsou preference při výběru partnera zkoumány dvěma způsoby: tradičně, prostřednictvím dotazování na důležitost vlastností partnera, a nově také zkoumáním prvotní fáze procesu výběru partnera za využití dat z internetových seznamovacích portálů [Fiore, Donath 2005;Potarca, Mills 2015;Skopek, Schulz, Blossfeld 2011]. Předpokládá se přitom, že údaje o prvním kontaktu při internetovém seznamování a odpovědi na něj jsou dobrým indikátorem preferencí a aspirací při výběru partnera [Skopek, Schulz, Blossfeld 2011].…”
Section: Partnerské Preference -Teoretická Východiska a Předchozí Studieunclassified